Pengaruh Patient Safety Leadership Walkrounds terhadap Budaya Keselamatan dan Implikasinya pada Pelaporan Kejadian Keselamatan pada Rumah Sakit - Eusebiusyuvens Chandra Waruwu; Arlette Suzy Puspa Pertiwi; R. Oke Andikarya (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Patient Safety Leadership Walkrounds (PSLW) were implemented at Siloam Hospital Bangka to enhance safety culture and incident reporting. This study aimed to evaluate the impact of PSLW on safety culture, the relationship between safety culture and safety-related incident reporting, and the effect of PSLW on safety-related incident reporting. A retrospective longitudinal survey was conducted to measure safety culture at Siloam Hospital Bangka in 2022 and 2024. Data were analyzed quantitatively using the Wilcoxon Rank-Sum test. Incident reports from the same years were compared using the Chi-Square test and correlated with safety culture through descriptive analysis. Safety culture survey scores increased from a composite average of 52% in 2022 to 63% in 2024. The Wilcoxon Rank-Sum test showed significant results for 16 of 34 questions (p<0.05). An increase in incident reporting occurred alongside improvements in safety culture. The number of incident reports rose from 317 in 2022 to 1,623 in 2024. The Chi-Square test demonstrated significant results. PSLW implementation enhanced both safety culture and safety-related incident reporting. Improvements in safety culture coincided with increased incident reporting numbers.